2021
DOI: 10.1080/14737159.2021.1944106
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic salivary biomarkers in oral cancer and oral potentially malignant disorders and their relationships to risk factors – A systematic review

Abstract: Introduction: Oral squamous cell carcinoma (OSCC) and oral potentially malignant disorders (OPMD) are a significant health burden globally. Smoking, alcohol and betel quid are the main risk factors. Lack of screening methods has been highlighted as a significant challenge in management. Salivary biomarkers are proposed as non-invasive diagnostic tools. The aim of this systematic review was to study salivary biomarkers reported in OSCC and OPMD. Specific objectives were to select a salivary biomarker panel suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Saliva-Based Biomarkers Saliva contains various biomarkers that signal disease, and it has great potential for early cancer diagnosis with cost-effective and easy collection, storage, transport and processing. A systematic literature review [25] has evaluated studies regarding possible saliva markers for PMOD and oral cancer in both unstimulated and stimulated morning saliva. These studies showed that most of the possible markers are proteins.…”
Section: Liquid Biopsiesmentioning
confidence: 99%
“…Saliva-Based Biomarkers Saliva contains various biomarkers that signal disease, and it has great potential for early cancer diagnosis with cost-effective and easy collection, storage, transport and processing. A systematic literature review [25] has evaluated studies regarding possible saliva markers for PMOD and oral cancer in both unstimulated and stimulated morning saliva. These studies showed that most of the possible markers are proteins.…”
Section: Liquid Biopsiesmentioning
confidence: 99%
“…The improved diagnostic technologies based on molecular biology highlighted the potential use of salivary biomarkers in the early detection of OSCC [ 102 ]. Proteomic platforms described around 200 peptides and proteins present in saliva and differentiated them into physiological and pathological conditions; furthermore, the salivary proteome for oral lesions and OSCC has been characterized [ 103 ], and over 100 potential salivary biomarkers for OSCC were identified [ 104 ].…”
Section: The Use Of Salivary Mmps As Biomarkers For Osccmentioning
confidence: 99%
“…Explorations into the use of salivary molecular markers that are specific to or preferential for oral cancer have suggested potential candidates for clinical applications, with transcriptomic and epigenomic markers being the most promising [12][13][14][15][16]. Furthermore, for epigenetic markers, our group and others have reported a better diagnostic accuracy when biomarker panels were used as opposed to single biomarkers [9,17,18]. However, it was observed that true genome-wide techniques, such as whole-genome bisulfite sequencing (WGBS) and reduced-representation bisulfite sequencing (RRBS), were not being utilized during methylome biomarker discovery, which may have limited the optimal biomarker selection [9,13].…”
Section: Introductionmentioning
confidence: 96%